An in-depth multidimensional review of hypertension in adolescents in relation to obesity: Risk approach management is the solution - Fadl, Azza Abul-; Al-Jawaldeh, Ayoub (Indian Journal of Child Health, 2021)
Background: The emergence of isolated high blood pressure (HBP) among adolescents and its relation to obesity needs to be investigated. Aim: This study aims to assess prevalence, underlying risk factors, and consequences of HBP among adolescents in Egypt. Methods: We consolidated findings from three studies. The first one examined 150 adolescents (age: 16–18 years) for HBP and obesity using body mass index (BMI); the second one studied 150 adolescents for the lifestyle risk factors in relation to depression, anxiety, general health score, and suicidal score (SS) using relevant tools; the third one was a nested case–control study of 60 obese versus 60 non-obese adolescents examined for HBP, BMI, lifestyles and dietary habits, biochemical markers as lipid profile, fasting blood sugar (FBS), insulin, and homeostatic model assessment for insulin resistance (HOMA-IR). Results: In Stage I, the prevalence of HBP was 8% of whom, 58.3% were obese. Stage II: Dietary risk behavior as junk foods (high in salt) and soft drinks was 75.3% and 80%, respectively, and was linked with a high SS. Smoking was associated with a high anxiety score (p<0.05) and not playing sports with a higher depression score (p<0.05). The nested case–control study for obese versus non-obese showed that HBP (both systolic and diastolic) was significantly higher in the obese. Consumption of junk foods, sugary drinks, and inactivity was significantly higher in the obese (p<0.05). Lipid profile, FBS, fasting insulin, and HOMA-IR were significantly higher in the obese group versus non-obese control group (p<0.05). Conclusion: Lifestyle and unhealthy diet are the underlying cause of HBP, obesity, and mental health problems including SS, atherosclerosis, and high FBS. Increasing awareness about risk factors and using them in clinical practice for early detection of HBP is recommended.